Analysis of PRM1 and PRM2 Polymorphisms in Iranian Infertile Men with Idiopathic Teratozoospermia - Fatemeh Dehghanpour; Farzaneh Fesahat; Seyed Mohsen Miresmaeili; Ehsan Zare Mehrjardi; Ahmad Honarju; Ali Reza Talebi (International Journal of Fertility and Sterility, 2019)
Single nucleotide polymorphisms (SNPs) in a number of genes involved in sperm maturation are considered as one of the main factors for male infertility. The aim of the present case-control study was to examine the association of SNPs in protamine1 (PRM1) and protamine2 (PRM2) genes with idiopathic teratozoospermia. In this case-control study, some SNPs in PRM1 (c.49 C>T, c.102 G>T and c.230A>C) and PRM2 (rs545828790, rs115686767, rs201933708, rs2070923 and rs1646022) were investigated in 30 idiopathic infertile men with teratozoospermia (case group) in comparison with 35 fertile men (controls). Genotyping of SNPs was undertaken using polymerase chain reaction (PCR)-direct sequencing. For PRM1, c.230A>C, as a synonymous polymorphism, was detected in both teratozoo- spermic men (heterozygous n=26, homozygous minor n=1) allele frequency C(48) A(52) and controls (heterozygous n=15, homozygous minor n=4). All cases and controls were genotyped for rs545828790 in PRM2, a missense poly- morphism, as well as rs115686767 and rs201933708, both of which synonymous variants. The findings showed an intronic variant in PRM2 (rs2070923) was also present in both groups. Also, rs1646022, a missense polymorphism, occurred in teratozoospermic men (heterozygous n=10, homozygous minor n=5) and controls (heterozygous n=13, homozygous minor n=2). However, there were no significant differences in SNPs of PRM1 and PRM2 between the two groups, however, for c.230A>C, the frequency of the CA genotype was significantly higher in infertile men with teratozoospermia (P=0.001). We demonstrate that PRM2 G398C and A473C polymorphisms were associated with the teratozoospermia and its genetic variation was in relation to semen quality, sperm apoptosis, and morphology in the Iranian population. This study is a preliminary study and presenting data as part of a future comprehensive study to clinically establish whether these gene polymorphisms are biomarkers for susceptibility to teratozoospermia.